2002
DOI: 10.1159/000066685
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Hispanic Women and Their Health Care Providers about Breast Cancer Risk Factors and Screening

Abstract: Objectives: The purpose of our study was to develop and evaluate an educational program for health care providers and patients on the topics of general breast cancer risk factors, breast cancer genetics, and breast cancer screening recommendations. The program was designed with specific emphasis on addressing the needs of medically underserved Hispanic women in Southern Texas. We also identified and compared perceptions of potential barriers to breast cancer screening. Methods: The educational program was pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…First, our sample was recruited from the Tampa Bay area and may not be representative of Hispanics from other regions of the United States. However, we did find many parallels between knowledge in our study population and that of studies of other Hispanic groups in Texas and New York (Strecker et al, 2002;Sussner et al, 2009). Second, there is currently controversy about if or how acculturation should be measured in the context of health research (Hunt et al, 2004).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…First, our sample was recruited from the Tampa Bay area and may not be representative of Hispanics from other regions of the United States. However, we did find many parallels between knowledge in our study population and that of studies of other Hispanic groups in Texas and New York (Strecker et al, 2002;Sussner et al, 2009). Second, there is currently controversy about if or how acculturation should be measured in the context of health research (Hunt et al, 2004).…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, less than 40% of women correctly answered questions related to the prevalence of BRCA mutations and risk reduction options related to ovarian cancer. In a study of 103 Hispanic patients enrolled in one of five primary clinics in a Texasbased study, less than one quarter of respondents was able to identify the amount of breast cancer due to hereditary predisposition (Strecker et al, 2002). Similarly, in our study, only 9% of women selected false to a question about whether half of all cases of breast cancer are attributed to a BRCA mutation.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Many of the barriers to seeking diagnosis and treatment identified by participants in our study have also been identified in the literature as barriers related to cancer screening, including cost, fear, embarrassment, and inaccurate risk perceptions (Coronado, et al, 2004; M.E.Fernandez, Palmer, & Leong-Wu, 2005; Strecker, Williams, Bondy, Johnston, & Northrup, 2002). However, much of the survivorship literature to date has focused primarily on issues facing non-Hispanic white women, particularly those living with breast cancer.…”
Section: Discussionmentioning
confidence: 57%
“…Of particular note are associations between knowledge, a central construct of health literacy, and use of genetic services and information. Limited knowledge of genetics among Latinos has been shown to impede both service provision (Browner et al, 2003;Urdaneta et al, 2002) and participation in services (Learman et al, 2003;Strecker, Williams, Bondy, Johnston, & Northrup, 2002;Thompson, Valdimarsdottir, Jandorf, & Redd, 2003). This is significant in light of research suggesting minimal levels of genetic knowledge among members of the Latino community (Hunt et al, 2005;Ramirez et al, 2006;Singer, Antonucci, & Van Hoewyk, 2004;Strecker et al, 2002;Urdaneta et al, 2002).…”
Section: Conceptual Frameworkmentioning
confidence: 99%